2009
DOI: 10.1007/bf03327621
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of field and model percentage drift using different types of hydraulic nozzles in pesticide applications

Abstract: ABSTRACT:In pesticide applications, small droplets are desired for better coverage and uniform distribution. Yet, small droplets have a problem: Drift, the movement of droplets off-target. Low drift nozzle produces fewer drift-prone droplets, < 100 µm, compared to standard hydraulic nozzles. In pesticide applications, standard hydraulic nozzles, hollow cone and flat fan nozzles are generally used by farmers. These nozzles have broad droplet spectrum and high proportion drift-prone droplets. Sample of drifted d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
15
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 24 publications
6
15
0
2
Order By: Relevance
“…The treatments can be placed in this order: GMV>GMG>GMO>MKM>ULVA. Results of the present study are comparable to results reported by YarpuzBozdogan et al, 12) who found that the initial residues of dicofol on strawberries after treatment with different spraying techniques ranged from 0.005 to 0.14 mg/kg. Data in Table 3 show that there is a clear positive relation of bifenthrin deposits on leaves with the spray volume applied.…”
Section: Deposit Of Bifenthrin After Applicationsupporting
confidence: 91%
“…The treatments can be placed in this order: GMV>GMG>GMO>MKM>ULVA. Results of the present study are comparable to results reported by YarpuzBozdogan et al, 12) who found that the initial residues of dicofol on strawberries after treatment with different spraying techniques ranged from 0.005 to 0.14 mg/kg. Data in Table 3 show that there is a clear positive relation of bifenthrin deposits on leaves with the spray volume applied.…”
Section: Deposit Of Bifenthrin After Applicationsupporting
confidence: 91%
“…That result was expected because it is well known from the literature that drift can be reduced by increasing the droplet size (Cross et al 2001;Yarpuz-Bozdogan and Bozdogan 2009). The ground deposits inside the orchard (BR-between rows) during coarse spraying were higher for both sprayer types, travel speeds and tree training systems when compared to fine spraying (compare BR data from Tables 5, 6).…”
Section: Results Of Drift Assessment During Spring Applicationssupporting
confidence: 53%
“…This pattern was also observed by Yarpuz-Bozdogan & Bozdogan (2009), who obtained largest drift values at a distance of 1 m from the crop, using an application rate of 200 L ha -1 on grassland. Beyond 20 m, the drift percentage was less than 1%.…”
Section: Resultssupporting
confidence: 76%